Visiting Picasso : poems - Barnes, Jim, 1933- (University of Illinois Press, 2007)
Annotation Jim Barnes's familiarity with the European poetic traditions has been deepened through long periods spent in France, Germany, and Italy, and through his translations of European poetry. In Visiting Picasso he repays Europe for its gifts to him in a series of poems that evoke the lush poetic history that ties European culture together, sometimes darkly. A heightened sense of place and purpose infuses the poems of Visiting Picasso with meaning drawn from actual landscapes, events, and observations.
Keywords: American poetry -- 20th century.; Poésie américaine -- 20e siècle.; POETRY -- American -- General.; FICTION -- General.; American poetry; 1900-1999; Electronic book.